Rehabilitating Juvenile Offenders through Islamic Education: Komunitas Pemuda Insyaf and the SDGs - Luthfi Syifa' Fauziyah; Muh. Nur Rochim Maksum; Muhammad Wildan Shohib; Alfan Rifai; Viky Nur Vambudi; Fahmi Ulum Al Mubarok; Mush’ab Umar Budihargo; Muhammad Dzikrul Fikri (Profetika: Jurnal Studi Islam, 2024)
Objective: Adolescence is a transitional phase that is vulnerable to behavioral deviations, including Juvenile Delinquency, which is now a global and national social problem. In this context, Islamic education plays an essential role as a means of moral and spiritual development that can rehabilitate problematic adolescents. Theoretical framework: The theoretical framework of this article combines the principles of Islamic education that include faith, sharia, and morals with the concept of inclusive education in SDG 4 and the social reintegration approach as the basis for character development and rehabilitation of ex-juvenile delinquents through communities such as KOPIKA. Literature review: Previous research has confirmed that Islamic education effectively prevents juvenile delinquency by forming character, strengthening self-control, and instilling moral values that shield from negative environmental influences. Methods: This qualitative research is field research conducted to uncover the contribution of Islamic education at KOPIKA in fostering ex-juvenile Delinquency perpetrators. Results: The results of the study show that KOPIKA has various non-formal Islamic coaching programs, such as Bikers Subuhan, Mas Bro, Sini Ramal, Algojo, Sinabung Kopi, Punk-Ngaosan, Hijrah Camp, and Silatu Ride. These programs contribute to increasing worship, bringing members closer to the Qur'an, and shaping members' social identity and concern. This initiative is relevant to SDG 4 because it brings inclusive and transformative education to vulnerable groups through a contextual and sustainable approach. Implications: These findings have important implications for strengthening the role of non-formal Islamic education in the social rehabilitation of troubled adolescents, as well as encouraging the creation of an inclusive, transformative, and sustainable education ecosystem by SDG 4 targets. Novelty: This research offers novelty in examining the contribution of community-based Islamic education to the rehabilitation of troubled adolescents and its relevance to the achievement of SDG 4.